Multi-objective PSO-TVAC for Environmental/Economic Dispatch Problem. (August 2015) - Hadji, Boubakeur; Mahdad, Belkacem; Srairi, Kamel; Mancer, Nabil
Abstract: In this paper a variant named time varying acceleration based particle swarm optimization (PSO-TVAC) proposed to enhance the solution of the combined environmental economic dispatch problem. The performances of the standard PSO are improved by adjusting dynamically the acceleration coefficient during process search to balance the exploitation and exploration capability. The proposed method is validated on IEEE 30-bus with quadratic cost function considering transmission losses and to 10 unit considering both valve point effect and total power losses. The simulation results are compared with those obtained by particle swarm optimization (PSO), no dominating sorting genetic algorithm (NSGA-II), and strength Pareto evolutionary algorithm (SPEA). The results demonstrate the efficiency of the proposed approach and show its simplicity and robustness to solve the environmental/economic dispatch problem.